Effect of Banana Stem Substitution on Sensory Acceptance, Physical, and Nutritional Characteristics of Stingray Fish Flos - Syamsiana Indah Cahyani; Siti Fathonah (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
Banana stem is a potential alternative food ingredient due to its fiber content and its limited utilization in processed food products. This study evaluated the effect of banana stem substitution in stingray fish floss on sensory acceptance, color characteristics, protein content, and moisture content. A Completely Randomized Design (CRD) consisting of four treatments was applied, namely F1 (0%), F2 (10%), F3 (15%), and F4 (25%) banana stem substitution. Sensory data were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney test, while nutritional quality data were subjected to ANOVA and Duncan’s multiple range test. Color evaluation was conducted digitally using the Color Identification application based on the RGB color system. The findings revealed that banana stem substitution did not significantly affect color attributes but significantly influenced aroma, texture, taste, and overall acceptability. Increasing the substitution level tended to produce a darker color in the fish floss. Significant differences were also observed in protein and moisture contents. Among all treatments, F4 (25% substitution) showed the highest overall acceptability score (7.7), with protein and moisture contents of 31.4% and 20.12%, respectively.